From Realism to Abstraction The Art of J. B. Taylor - Davies, Adriana A. (Art in Profile: Canadian Art and Architecture, 2014)
Highly respected as an Alberta artist and teacher, J. B. (Jack) Taylor (1917-1970) is best known for his representational, semi-abstract, and abstract paintings of the Canadian Rocky Mountains. Taylor's initial influences were the American landscape painters of the latter half of the nineteenth century. Ultimately, he moved from a more traditional representation of nature to an intuitive perception of the essential elements of landscape rock, water, and sky as impacted by light. Rather than presenting mountains in all their majesty, using acrylics and other media, he captured the aura of the mountains in a unique and abstract style.